Stress-Deformation Mechanisms of Tunnel Support in Neogene Red-Bed Soft Rock: Insights from Wireless Remote Monitoring and Spatiotemporal Analysis - Jin Wu; Zhize Han; Yunxing Wang; Feng Peng; Geng Cheng; Jiaxin Jia (Buildings, 2025)
Red-layer soft rock has characteristics such as softening when encountering water, loose structure, and significant rheological properties. In tunnel engineering, it is necessary to sort out and analyze the stress characteristics of its support structure. This paper focuses on the mechanical behavior and support effect during the construction of Neogene red-layer soft rock tunnels. Through field monitoring, it explores the mechanical characteristics of Huizhou Tunnel under complex geological conditions in depth. This study adopted a remote wireless monitoring system to conduct real-time monitoring of key indicators including tunnel surrounding rock pressure, support structure stress, and deformation, obtaining a large amount of detailed data. An analysis revealed that the stress experienced by rock bolts is complex and varies widely, with stress values between 105 and 330.5 MPa. The peak axial force at a depth of 2.5 m reflects that the thickness of the loosened zone in the surrounding rock is approximately 2.5 m. The compressive stress in the steel arches of the primary support does not exceed 305.3 MPa. Shotcrete effectively controls the surrounding rock deformation, but the timing of support installation needs careful selection. The stress in the secondary lining is closely related to the primary support. The research findings provide an important theoretical basis and practical guidance for optimizing the support design of red-bed soft rock tunnels and enhancing construction safety and reliability.